Revision of the circumglobal deep-sea genus Leucicorus (Teleostei, Ophidiidae) with two new species - Schwarzhans, Werner W.; Nielsen, Jørgen G.; Mundy, Bruce C. (Zootaxa, 2022)
The rare deepsea ophidiid genus Leucicorus was described by Garman (1899) based on L. lusciosus Garman, 1899 caught in the East Pacific. Until 1973 only three additional specimens were caught of which two from the East Pacific belong to L. lusciosus and one from off Hawaiʽi is an undescribed species here described as L. lentibus n. sp. In 1973 a Soviet expedition to the Caribbean Sea trawled 18 specimens from abyssal and hadal depths and based on this material a second Leucicorus species was described, L. atlanticus Nielsen, 1975. Since then eight Leucicorus specimens from the Indo-Pacific and Atlantic Oceans have been caught of which two from the West Atlantic belong to a new species, L. gerringerae n. sp., herein described, four to L. atlanticus and two remain as Leucicorus sp. About 35 demersal Leucicorus specimens have been observed and photographed by ROV (remotely operated vehicle) at depths of 3804-5768 meters in the Pacific Ocean.